Implementasi Model Problem Based Learning dalam Pembelajaran Bahasa Indonesia di Kelas VII SMP Negeri 20 Kota Bengkulu - Zahro, Afifah Eka Az; Gumono, Gumono; Kurniawan, Rio (Jurnal Korpus, 2025)
The aim of this research is to explain how the problem-based learning model is implemented in Indonesian language learning in class VII of SMP Negeri 20 Bengkulu City. Indonesian language teachers who teach in class VII are the subjects of this research, which focuses on the learning process using a problem-based learning model. The research method is descriptive qualitative, and data collection techniques include observation, interviews and documentation. The results of the research show that at stage one, students are oriented towards the problem. Not implemented by the Teacher. And in the second stage, organizing students to solve problems. It has been implemented by the teacher. Then the third stage, namely guiding problem solving independently or in groups, is carried out by the teacher. Next, the fourth stage presents the results of the work/discussion. It has also been implemented by the Master. However, the fifth stage, solving and completing the problem solving process which has not been optimally implemented by the teacher.